Changing Pattern of wetlands: A Case Study of Damak Municipality, Jhapa District, Nepal - Pokhrel, Puspa Lal (Journal of Advance Research in Food, Agriculture and Environmental Science (ISSN 2208-2417), 2020)
The climate of Damak was unhealthy until 1965 A.D. The D. D.T. spray program started here only since 1963. Before 1963 Damak was a home of malaria. This area was dreadful due to the wide due to the wide-presence of poisonous creatures like cobras, Karent (Bungarus lividus), and scorpions. There were a lot of oxbow lake, marshes, quicksand, Holies and swamps inside the tick and dense forests of Damak. It used to be a very difficult situation to the local cowboys to rescue the new foot travelers from hill areas who plunged into the marshes. But Damak, these days, has lost its past physical landscape. The people who visited Damak in the 1960's and 1970's can hardly recognize present Damak. The actual identify of Damak still are the marshes and wetland areas. The name " Damak" itself is derived from the word "Daldal" which means "marshes" in English. In Dhimal language, " Damdam" means "Daldal" meaning " marshy". So from " Damdam" the name " Damak" was derived. This land is hard to plough as it is marshy. The paddy is planted only after digging the field with a spade. So the meaning of Damak reflects "shiny bright". As we step on one part at marshy land (Damdam place), the other part produces shiny fountains. With references to legends and proofs, Damak can be said to have been a marshy area before 1960.